Constructability Concepts in West Port Highway in Malaysia - Nima, Mekdam A.; Abdul Kadir, Mohd Razali; Jaafar, Mohd Saleh; Alghulami, Riadh G. (American Society of Civil Engineers, 2002)
This paper presents a case study of the applications and nonapplications of constructability concepts to illustrate, in a practical way, the impact that these concepts can have on a project's success. This case study, which conveys an important message with regard to the application of constructability concepts, was purposely chosen from among prestigious projects in peninsular Malaysia. The basic message, as viewed by the interviewees, is that applying these constructability concepts will enhance a project's constructability, consequently optimizing the schedule, cost, and quality of the project for the benefit of all the parties involved. The interviewees for the case study agreed that the applied constructability concepts were derived from their own experience and not based on any existing formal program. The absence of a systematic technique for transferring construction experience and knowledge to all the participants in all phases of a construction project is the reason behind the lack of constructability in our construction industry today.